Forest canopy microclimate regulation during the drought year 2018 at the Leipzig Canopy Crane site - Ronny Richter (PANGAEA, 2022)
Tree canopies are considered to effectively buffer climate extremes and to mitigate climate change effects. Droughts, which are predicted to become more frequent in the course of climate change, might alter the microclimatic cooling potential of trees. However, our understanding of how microclimate at the tree canopy level is modulated by environmental and tree characteristics and their interactions is still limited. Here, we investigated canopy temperature regulation for five mature co-occurring tree species for two contrasting hydrological situations during the severe drought in 2018.